Bio-manured Multi-Ratooning Enhances Sugarcane Plant-Ratoon System Productivity - Srivastava, T. K.; Singh, K. P.; Singh, Pushpa (Indian Farming, 2015)
Bio-manuring in sugarcane multiratooning improves the rhizosphere micro-climate and structure as compared to inorganic fertilizers and promotes the restoration of return of easily decomposable organic compounds in the soil rhizosphere with positive influence over organic carbon content, microbial activities and soil physical properties. Sugarcane cultivation using biomanures as source of nutrients can be ensured to be more profitable as compared to that with the use of recommended levels of NPK in multi-ratooning system. Further, more number of ratoons can be successfully raised with the use of bio-manures leading to enhanced overall productivity and profitability of the sugarcane cropping system.